Lyapunov approach on a homogeneous family of controllers for robotic manipulator - Jang, Wilson (2019)
Second order sliding mode has been successfully implemented for solution of real problems for its inherent features such as finite-time convergence and robustness to disturbances. For the first order sliding modes, it is common to deal with the issues of stability, robustness, and convergence rate of the equilibrium by means of a Lyapunov approach. For higher order sliding modes, however, a similar treatment has not been developed until recently. The focus of this thesis is the construction of strong Lyapunov function, i.e. for which its time derivative can be upper bounded by negative-definite functions, for the design of control strategies for robotic manipulator, which is a nonlinear system, subject to combinations of parametric uncertainty, bounded disturbances, actuator saturation, and output feedback.